Firm Self-Service Technology Readiness - Ramaseshan, Balasubramani; Kingshott, Russel; Stein, A. (Emerald Group Publishing, 2015)
Purpose: Technological advances and new business models have contributed to the usage of self-service technology (SST) by firms. As SST continues to create organisational efficiencies, firms have jumped on the bandwagon without considering their own readiness to use SST. To date, there has been no systematic attempt to develop a valid scale of firm SST readiness and assess its influence on firm performance. This paper presents and validates a multidimensional firm SST readiness scale. Design/methodology/approach: A series of studies was conducted for the development and validation of the firm SST readiness scale. Study 1 included generating items from semi-structured interviews with managers and an extensive literature review. Study 2 comprised item reduction and identifying the dimensionality of the scale through exploratory factor analysis (n = 177 participants from service organisations). The reliability and validity of the scale were tested in Study 3 by performing confirmatory factor analysis using data obtained from managers of service organizations in the United States (n = 257). Study 4 measured the predictive validity of the firm SST readiness instrument using several structural models. Findings: This paper proposes a new multidimensional construct labelled ‘Firm SST Readiness’, consisting of four dimensions: managerial acquiescence, customer alignment, employee engagement, and channel integration. The predictive validity of the new scale on two key firm outcome variables: customer value and firm performance is also demonstrated. Originality/value: This is the first study to provide a comprehensive, psychometrically sound, and operationally valid measure of firm SST readiness.